Two-Dimensional NMR Spectroscopy: A Powerful Tool for the Investigation of Molecular Structure and Dynamics - Richard R. Ernst (CHIMIA)
Today chemical research is hardly conceivable without nuclear magnetic resonance. It has proved to be an exceedingly rich source of information for exploring the structure of molecules in solution, for the investigation of solid materials, and for the study of molecular dynamics. In order to cope with the overwhelming information content, an extension to two-dimensional spectroscopy turned out to be indispensibel. Two-dimensional spectroscopy has contributed, since its introduction twelve years ago, a large number of new powerful techniques for the elucidation of coupling networks by 2D correlation spectroscopy, for the measurement of internuclear distances by 2D cross-relaxation spectroscopy, and for the investigation of chemical exchange networks by 2D exchange spectroscopy. These new techniques are particularly useful for the analysis of large molecules in chemistry and in biology.